CLINICAL APPLICATION OF BONE MORPHOGENETIC PROTEIN ON FRACTURE HEALING PROCESS - Riko Febrian Kunta Adjie (Journal Orthopaedi and Traumatology Surabaya, 2017)
Delayed union or non-union often occurs in bone healing fracture process. The clinical application of Bone Morphogenetic Proteins (BMPs) has helped an increasing number of patients achieve bone regeneration in clinical area lacking simple solutions for difficult bone healing situations. Many researches has proved that BMPs improved fracture healing regeneration. In this review article, introduction and current clinical issues are summarized on efficacy and function of BMPs. Currently, rhBMP-2 and rhBMP-7 have shown clinical significance but other subfamily members of BMPs still lacked of evidence.